A new desmid (Zygnematophyceae, Streptophyta) species from New Zealand, Cosmarium wilsonii spec. nov. Issue 1 (2nd January 2020) - Williamson, David B.; Carter, Christopher F.
ABSTRACT: A small pond in Hinewai Reserve, Banks Peninsula, Canterbury has revealed a phytoplankton bloom consisting of an unusually minute desmid which has consequently been difficult to observe. It is described, assigned to the genus Cosmarium and compared with superficially similar species. It has unique features which justify assigning it to a new species Cosmarium wilsonii David B. Williamson & C.F. Carter. It is named after the Reserve kaitiaki (manager) Dr H. D. Wilson.